Autoxidation mechanism for atmospheric oxidation of tertiary amines: Implications for secondary organic aerosol formation. (June 2021) - Ma, Fangfang; Xie, Hong-Bin; Li, Mingxue; Wang, Sainan; Zhang, Renyi; Chen, Jingwen
Abstract: Tertiary amines are one kind of identified amines in the atmosphere. Here, the atmospheric oxidation mechanism and kinetics of tertiary amines were investigated by using computational methods. As proxies of these amines, trimethylamine (TMA) and triethylamine (TEA) have been selected. Results indicate that N-containing peroxy radicals (NRO2 ⋅), which are key intermediates in ⋅OH initiated oxidation of TMA and TEA, can follow a so-called autoxidation mechanism (a chain reaction of H-shift followed by O2 addition) even on the condition of high NO/HO2 ⋅ concentration. Such unique mechanism can be ascribed to the ability of N-atom in facilitating the unimolecular H-shift of NRO2 ⋅ and the absence of H-atoms on N-atom. However, different from TMA reaction system, the pathway dissociating into fragmental products can compete with the autoxidation pathway for TEA system. More importantly, TEA reaction system cannot lead to the formation of products with high O/C ratio due to the autoxidation pathway terminated by the release of fragmental molecules. Such difference can be corroborated by previously observing lower secondary organic aerosol yield of TEA oxidation than that of TMA oxidation. The unveiled mechanism enhances current understanding on atmospheric fate of amines and autoxidation mechanism. Graphical abstract: Image 1 Highlights: Atmospheric oxidation of tertiary amines TMA and TEA can follow an autoxidation mechanism. Reasons for different contributions of TMA and TEA oxidation to SOA formation were revealed. Atmospheric chemistry of tertiary amines is structure-dependent.